Variation in mode of physical activity by ethnicity and time since immigration: a cross-sectional analysis - Ardern Chris I; Meisner Brad A; Dogra Shilpa (BMC, 2010)
Abstract Background Physical activity (PA) levels are known to be significantly lower in ethnic minority and immigrant groups living in North America and Europe compared to the general population. While there has been an increase in the number of interventions targeting these groups, little is known about their preferred modes of PA. Methods Using three cycles of the Canadian Community Health Survey (cycles 1.1, 2.1, 3.1; 2000-2005, n = 400,055) this investigation determined PA preferences by self-ascribed ethnicity (White, South Asian, South-East Asian, Blacks, Latin American, West Asian, Aboriginal persons and Other) and explored variation in PA preference across time since immigration categories (non-immigrant, established immigrant [> 10 years], and recent immigrant [≤ 10 years]). PA preferences over the past three months were collapsed into eight categories: walking, endurance, recreation, sports, conventional exercise, active commuting, and no PA. Logistic regression models were used to estimate the odds of participating in each PA across ethnicity and time since immigration compared to Whites and non-immigrants, respectively. Results Compared to Whites, all other ethnic groups were more likely to report no PA and were less likely to engage in walking, with the exception of Aboriginal persons (OR: 1.25, CI: 1.16-1.34). Further, all ethnic groups including Aboriginal persons were less likely to engage in endurance, recreation, and sport activities, but more likely to have an active commute compared to Whites. Recent and established immigrants were more likely to have an active commute and no PA, but a lower likelihood of walking, sports, endurance, and recreation activities than non-immigrants. Conclusion Ethnic minority groups and immigrants in Canada tend to participate in conventional forms of exercise compared to Whites and non-immigrants and are less likely to engage in endurance exercise, recreation activities, and sports. Health promotion initiatives targeting ethnic and immigrant groups at high-risk for physical inactivity and chronic disease should consider mode of PA preference in intervention development.